Human Natural Killer Cells Downregulate Zap70 and Syk in Response to Prolonged Activation or DNA Damage - Pugh, Jason L. (J Immunol, 2017)
The extent of NK cell activity during the innate immune response affects downstream immune functions and, ultimately, the outcome of infectious or malignant disease. However, the mechanisms that terminate human NK cell responses have yet to be defined. When activation receptors expressed on NK cell surfaces bind to ligands on diseased cells, they initiate a signal that is propagated by a number of intracellular kinases, including Zap70 and Syk, leading eventually to NK cell activation. We assayed Zap70 and Syk content in NK cells from healthy human donors, and identified a subset of NK cells with unusually low levels of these two kinases. We found that this Zap70(low)Syk(low) subset consisted of NK cells expressing a range of surface markers, including both CD56(hi) and CD56(low) NK cells. Upon in vitro stimulation with target cells, Zap70(low)Syk(low) NK cells failed to produce IFNγ, and lysed target cells at one-third the capacity of Zap70(hi)Syk(hi) NK cells. We determined two independent in vitro conditions that induce the Zap70(low)Syk(low) phenotype in NK cells: continuous stimulation with activation beads, and DNA damage. The expression of inhibitory receptors, including NKG2A and inhibitory killer immunoglobulin-like receptors (KIR), was negatively correlated with the Zap70(low)Syk(low) phenotype. Moreover, expression of multiple KIR reduced the likelihood of Zap70 downregulation during continuous activation, regardless of whether NK cells had been educated through KIR-HLA interactions in vivo. Our findings show that human NK cells are able to terminate their functional activity without the aid of other immune cells through the downregulation of activation kinases.